Ameliorative Role of Vitamin C against Toxicity by Food Additive in the Male Rats - Afyaa Sabah Nasir (Journal of Global Pharma Technology, 2016)
Food additives are widely used in the food for example MSG present in variety types of food so the current study is proposed to evaluate the protective role of vitamin C in the male white rats for 30 days. The results showed the significant increase (p<0.05) in the levels of liver functions tests and lipid profile as well as significant decrease (p<0.05) in the biochemical parameters include total protein and albumin. Also, the histological examination for liver tissues demonstrate the histopathological change include degeneration, bleeding and necrosis. So that, the results appear MSG is highly toxic and treatment with vitamin C can to decrease the toxic effect for MSG in the biochemical parameters and histological changes in the liver tissues.Keywords: MSG, Liver functions, Vitamin C and rats.